Kebijakan Penyelenggaraan Percepatan Pembangunan Sanitasi Permukiman Di Daerah - Pratiwi, Vony Febriana (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2023)
Sanitation programs are an integral part of efforts to maintain public health. Good sanitation includes waste management and environmental cleanliness and provides safe and adequate access to clean water and sanitation facilities. By understanding the importance of sanitation programs, governments, non-governmental organizations, and communities can work together to increase everyone's access to adequate sanitation. This is an essential step in achieving sustainable development goals and improving society's overall health and well-being. This research uses a qualitative method with a descriptive approach. This research data collection method uses a descriptive-normative method. Although most countries have national policies and plans to support sanitation, only some countries have allocated sufficient human and financial resources to implement them. The policy in Indonesia for implementing sanitation programs was formed through Minister of Home Affairs Regulation Number 87 of 2022 concerning the Acceleration of Sustainable Sanitation Services in Regions for 2022-2024. However, future implementation will experience stagnation, considering that the regulation is limited to only two years, namely 2022 to 2024. So, to anticipate this, the government must immediately form a regulatory platform for implementing the sanitation program at the end of the existing regulations.